Association of Serum Phosphate and Related Factors in ESRD-Related Vascular Calcification. (25th May 2011) - Zheng, Cai-Mei; Lu, Kuo-Cheng; Wu, Chia-Chao; Hsu, Yung-Ho; Lin, Yuh-Feng
Abstract : Vascular calcification is common in ESRD patients and is important in increasing mortality from cardiovascular complications in these patients. Hyperphosphatemia related to chronic kidney disease is increasingly known as major stimulus for vascular calcification. Hyperphosphatemia and vascular calcification become popular discussion among nephrologist environment more than five decades, and many researches have been evolved. Risk factors for calcification are nowadays focused for the therapeutic prevention of vascular calcification with the hope of reducing cardiovascular complications.